TINGKAT LIKUIDITAS PADA KEBIJAKAN DIVIDEN BERDASARKAN PROFITABILITAS, LEVERAGE DAN INVESTMENT OPPORTUNITY SET - Karina Ardhia Hendrayani; Sri Hermuningsih (SEGMEN: Jurnal Manajemen dan Bisnis, 2022)
This study aims to test and analyze the effect of profitability, leverage and investment opportunity set on cash dividend policy with liquidity as moderating variable. The research population includes 4 state-owned bank companies listed on the Indonesia Stock Exchange (IDX) for the period 2008-2019. The company’s cash dividend policy is a difficult financial decision for the management of the company, so it is necessary to consider the factors that affect it. Data analysis techniques used are simple regression analysis, and Moderated Regression Analysis (MRA). The results of this study show that profitability and investment opportunity set have a significant positive effect on cash dividend policy, while leverage has a significant negative effect on cash dividend policy. Liquidity is able to moderate the influence of profitability, leverage and investment opportunity set on cash dividend policy.Keyword(s) : Dividend Policy, Profitability, Leverage, Investment Opportunity Set, Liquidity